The United States of Trump : [large type] how the President really sees America - O'Reilly, Bill (Thorndike Press large print core series, 2019)
Drawing on exclusive interview materials and deep research, this book is an insider's portrait of the 45th President that includes previously undisclosed details about Trump's childhood, family life and career.